Degradation model of a linear-mode LED driver and its application in lifetime prediction - Lan, Song (2015)
The degradations of a linear-mode LED driver under different voltage stresses are studied. This driver provides a constant current when the output voltage is biased greater than a knee-point voltage. During the stress tests, the knee-point voltage is found to increase due to the aging of the output transistor in the driver. As the knee-point voltage exceeds the applied output voltage, the output current cannot be maintained as constant, and the driver is considered failure. Therefore, the lifetime of the driver can be estimated from the knee-point voltage degradation. In this paper, a lifetime extrapolation method is proposed based on an internal circuit degradation mechanism. The correlations between the degradation model parameters and the applied stress are deduced, and the lifetime of the driver under different voltage stresses can be predicted with this correlation.